Nutrition and the ageing brain: Moving towards clinical applications - Flanagan, E; Lamport, D; Brennan, L; Burnet, P; Calabrese, V; Cunnane, SC; de Wilde, MC; Dye, L; Farrimond, JA; Emerson Lombardo, N; Hartmann, T; Hartung, T; et al. (Elsevier, 2020)
The global increases in life expectancy and population have resulted in a growing ageing population and with it a growing number of people living with age-related neurodegenerative conditions and dementia, shifting focus towards methods of prevention, with lifestyle approaches such as nutrition representing a promising avenue for further development. This overview summarises the main themes discussed during the 3rd Symposium on “Nutrition for the Ageing Brain: Moving Towards Clinical Applications” held in Madrid in August 2018, enlarged with the current state of knowledge on how nutrition influences healthy ageing and gives recommendations regarding how the critical field of nutrition and neurodegeneration research should move forward into the future. Specific nutrients are discussed as well as the impact of multi-nutrient and whole diet approaches, showing particular promise to combatting the growing burden of age-related cognitive decline. The emergence of new avenues for exploring the role of diet in healthy ageing, such as the impact of the gut microbiome and development of new techniques (imaging measures of brain metabolism, metabolomics, biomarkers) are enabling researchers to approach finding answers to these questions. But the translation of these findings into clinical and public health contexts remains an obstacle due to significant shortcomings in nutrition research or pressure on the scientific community to communicate recommendations to the general public in a convincing and accessible way. Some promising programs exist but further investigation to improve our understanding of the mechanisms by which nutrition can improve brain health across the human lifespan is still required.